Medium range forecasting in India- An over viewMedium range forecasting in India- An overview (MAUSAM, 1990)
Medium range forecasting alms at predicting meteorological parameters with a validity ranging from 3 to 10 days, Work on medium range forecasting was taken up in India in the late fifties and a special unit was set up for medium range forecasting research, As a first step preparation of data base was required, Statistical and synoptic-cum-statistical techniques developed for prediction of pentad (5-day) and weekly rainfall anomalies for a group of sub-divisions are reviewed in the paper.0